Public sentiment oscillations, information structure and marketing efforts in live-stream supply chains - Jidi Zhao; Wanglai Li; Huizhang Shen (Asia Pacific Journal of Marketing and Logistics, 2026)
Purpose This study investigates how public sentiment oscillations induced by live-stream influencers shape demand fluctuations and affect supply chain decisions under different information structures. Design/methodology/approach Drawing on live-streaming contexts, this study models the interaction between suppliers and influencers and examines equilibrium outcomes under different information structures using analytical and numerical methods. Findings First, when adjustment cost for demand fluctuations are high, suppliers become insensitive to sentiment shocks, resulting in rigid operations. Second, information structure shapes how public sentiment affects the supply chain. Especially under information asymmetry, large public sentiment oscillations characterized by high uncertainty amplify risks. Moreover, such uncertainty induces a redistribution effect, consistently harming suppliers while potentially benefiting influencers depending on the wholesale pricing structure. Third, marketing efforts reshape the impact of public sentiment. Specifically, marketing cost allocation alters suppliers' wholesale price adjustment thresholds under heightened uncertainty, which in turn redistributes the effects of uncertainty between both parties. Originality/value This study contributes to the live-stream e-commerce literature by uncovering how influencer-driven public sentiment oscillations propagate through supply chain interactions, providing new insights into managing demand fluctuations in digital commerce environments.